The The business longevity of SMEs based on entrepreneurial orientation and government policies in facing disruption challenges - Abdul Azis Bagis; Akram Sukma; Santi Nururly (Jurnal Siasat Bisnis, 2023)
Purpose ─ This paper aims to examine the role of entrepreneurial orientation for SMEs in building business continuity in eastern Indonesia and highlight strengthening government support for the sustainability of post-covid SME entities. Design/methodology/approach ─ A random sampling approach was used to select the respondents, with closed questions used for a sample of 400 SME owner-managers in eastern Indonesia using the structural equation modelling technique (PLS-SEM). Findings ─ The results show that the ability of SME owner-managers to build business longevity is determined more by their strong entrepreneurial orientation than by government support. In the context of this study, the government’s support policy for SMEs in eastern Indonesia is ineffective. Limitations/research implications – This research selects the characteristics of the living company by Geus, which positions business entities as living beings, as an indicator of business longevity. Practical implications - Based on research results, the sustainability of SMEs in eastern Indonesia can be built based on the owner-managers entrepreneurial orientation. Meanwhile, government support still needs to be maximized. Originality/value ─ The contribution of three determinants of government support to SMEs is analyzed to determine the acceleration of the survival of SMEs after Covid.